2017
DOI: 10.1053/j.semnuclmed.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule PET Tracers for Imaging Proteinopathies

Abstract: In this chapter, we provide a review of the challenges and advances in developing successful positron emission tomography (PET) imaging agents for three major types of aggregated amyloid proteins – amyloid-beta (Aβ), tau, and alpha-synuclein (α-syn). These three amyloids are involved in the pathogenesis of a variety of neurodegenerative diseases, referred to as proteinopathies or proteopathies, that include Alzheimer’s disease, Lewy body dementias, multiple system atrophy, and frontal temporal dementias among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 253 publications
0
98
0
Order By: Relevance
“…Specific high-affinity ligands for misfolded a-synuclein pathology suitable for brain imaging have been difficult to identify [125,126]. SIL23 is not sufficiently selective in the presence of Ab or tau pathology.…”
Section: Targeting A-synucleinmentioning
confidence: 99%
“…Specific high-affinity ligands for misfolded a-synuclein pathology suitable for brain imaging have been difficult to identify [125,126]. SIL23 is not sufficiently selective in the presence of Ab or tau pathology.…”
Section: Targeting A-synucleinmentioning
confidence: 99%
“…Other studies also support that moderate to frequent striatal (and cortical) diffuse Aβ plaques are PET detectable (Beach, Thal, Zanette, Smith, & Buckley, ). For a more in‐depth review of amyloid PET imaging in AD the reader is referred to Mathis, Lopresti, Ikonomovic, & Klunk, .…”
Section: Overview Of Amyloid Plaque Pathology and Pet Imaging Of Admentioning
confidence: 99%
“…Studies of DS also reported accumulation of alpha‐synuclein aggregates in Lewy bodies and neurites in neocortex and amygdala (Davidson et al, ; Lippa, Schmidt, Lee, & Trojanowski, ) and TDP‐43 in dentate gyrus granule cells (Davidson et al, ; Lippa et al, ). Though none of currently available amyloid PET ligands binds to tau, alpha‐synuclein, or TDP‐43 aggregates, the relationship of these lesions to amyloid is an important avenue of investigation, in relation to development of dementia in people with DS, especially if PET ligands specific for alpha‐synuclein and TDP‐43 are developed successfully (Mathis et al, ).…”
Section: Neuropathology Substrates Of Amyloid Pet Ligands In the Ds Bmentioning
confidence: 99%
“…However, unlike Alzheimer's disease, where similar observations have inspired the initiation of “prevention” trials in individuals either genetically at risk (DIANE) or bearing imaging evidence of brain amyloid pathology (A4), prodromal PD is characterized by an accumulation of relatively nonspecific and unrelated symptoms and signs such as hyposmia, rapid eye movement sleep behavior disorder, and autonomic dysfunction, thus making recognition of the prodromal PD difficult in the general practice environment. Furthermore, we lack a biomarker of PD pathology that has the discriminative and predictive abilities of amyloid PET imaging . To enable the conduct of true prevention trials in PD, not only do we need strongly predictive biomarkers but also we need to educate general internal medicine, geriatric, and primary care physicians as well as the lay community about the importance of recognizing prodromal PD.…”
Section: Key Advances In Pd Clinical Sciencesmentioning
confidence: 99%
“…13,14 A second major challenge is that there currently is no established method to assess target engagement in the brain for therapies that target a-synuclein. [15][16][17] The key species of a-synuclein aggregates that is pathogenic and causes neurodegeneration remains to be established, and consequently, it is unknown if a FIG. 1.…”
Section: Challenges Facing A-synuclein Therapeutic Approachesmentioning
confidence: 99%